Mejoramiento de los procesos en la cooperativa de producción cafetalera los ángeles, para incrementar su productividad y la calidad de sus productos - Morán Yánez, Jampier Adonis (2023)
This project focuses on the design and improvement of production processes at the Los Angeles Coffee Cooperative with the aim of increasing efficiency and productivity. It was identified that the lack of efficient process design was affecting the cooperative's performance. The implementation of the ISO 9001 methodology was proposed to optimize processes. Research reveals that implementing the ISO 9001 methodology has the potential to reduce defects, improve quality, increase customer satisfaction, and reduce costs. Furthermore, the advantages of this methodology for the coffee sector are highlighted. The project also addresses the redistribution of space in the cooperative, the implementation of inspection areas and other strategic changes to improve efficiency.